Antimüllerian hormone and antral follicle count are lower in female cancer survivors and healthy women taking hormonal contraception - Johnson, Lauren N.C.; Sammel, Mary D.; Dillon, Katherine E.; Lechtenberg, Lara; Schanne, Allison; Gracia, Clarisa R. (Fertility and sterility, 2014)
To determine the impact of hormonal contraception (HC) on markers of ovarian reserve, including antimüllerian hormone (AMH) and antral follicle count (AFC). Longitudinal prospective cohort. University hospital. Young adult female cancer survivors and healthy similar-age women. None. Participants were followed annually to determine hormone levels and for transvaginal ultrasound. Subjects who used HC within the preceding 3 months were considered to be exposed. Linear mixed effects models were used to incorporate repeated measures and adjust for potential confounders. A total of 249 women (126 survivors, 123 control subjects; average age 25.5 years) were followed for an average of 2.1 visits and 2.15 years. After adjusting for confounders, AMH was found to be 21% lower among survivors using HC and 55% lower among control subjects using HC (relative risk [RR] 0.79, 95% confidence interval [CI] 0.68–0.93; and RR 0.45, 95% CI 0.30–0.68; respectively). AFC was 20% lower among survivors and control subjects using HC (RR 0.80, 95% CI 0.69–0.93). When considering an individual subject, AMH was 17%–35% lower when a subject had recently used HC than when she had not (survivors: RR 0.83, 95% CI 0.75–0.93; control subjects: RR 0.65, 95% CI 0.55–0.78), and AFC was 11% lower (RR 0.89, 95% CI 0.82–0.96). Additive HC exposure across multiple visits was not associated with differences in AMH or AFC. AMH and AFC are significantly lower among women with recent exposure to HC. AMH and AFC should be interpreted with caution when measured in the setting of recent hormone use.